Paraprofessionals' Perceptions of Violence and Training: Investigating an Understudied Group - Wentworth, Bryan (My University, 2015)
Paraprofessionals often work in a variety of roles directly with students with disabilities. Previous research on paraprofessionals has indicated that they are often undertrained for the jobs they are asked to perform. In addition, much of the current research on school violence has not included paraprofessionals and other support staff. This study sought to uncover paraprofessionals' perceptions of violence they have experienced and the training they have received. Data was collected through interviews and a questionnaire.
Keywords: Schools; Educational Leadership; Paraprofessional Training; Education; Support Staff; Special Education; School Violence; Violence; Paraprofessionals